Mosquito ecology surveillance and analysis in Yangpu District， Shanghai from 2019 to 2023 - LU Chonghua; ZHANG Jie; ZONG Lili (Shanghai yufang yixue, 2025)
ObjectiveTo delineate the species composition structure and seasonal density fluctuations of mosquito populations in Yangpu District, Shanghai, and to provide scientific insights for the prevention and control of vector-borne diseases.MethodsA total of 12 monitoring sites from different habitats were selected to conduct adult mosquito monitoring using the CO2 trap light method during 2019‒2023, elucidating the temporal and spatial distribution and change patterns of mosquito populations and densities in Yangpu District.ResultsFrom 2019 to 2023, a total of 1 321 female mosquitoes was captured, with an overall density of 0.16 case·(lamp·h)-1. The species identified were predominantly Culex pipiens pallens (87.28%), followed by Aedes albopictus (12.64%), and Culex tritaeniorhynchus (0.08%). Seasonal distribution showed a typical single-peak pattern, with June‒August being the peak period. In terms of habitat distribution, the highest mosquito population density was found in residential areas [0.18 case·(lamp·h)-1], followed by hospitals [0.13 case·(lamp·h)-1] and parks [0.11 case·(lamp·h)-1]. Culex pipiens pallens was the dominant species in all habitats, with a density of [0.14 case·(lamp·h)-1]. Notably, there was a statistically significant difference in the composition of Culex pipiens pallens and Aedes albopictus among the three habitats mentioned (χ2=38.396, P<0.001; χ2=36.790, P<0.001). The mosquito density of the 12 streets from high to low is Changhai Road, Pingliang, Yinhang, Xinjiangwan City, Yanji, Daqiao, Wujiaochang, Kongjiang, Changbai New Village, Jiangpu, Siping and Dinghai.The distribution of mosquito density was relatively balanced across different communities (H=1.559, P=1.000).ConclusionThe results of CO2 trap light monitoring reveals a relatively low density of adult mosquitoes in Yangpu District, with Culex pipiens pallens as the predominant species, and summer being the peak season for mosquitoes. In light of the threat of mosquito-borne diseases such as dengue fever, more effective and evidence-based mosquito control strategies, aligning with the distribution and behavioral patterns of mosquitoes, should be developed.